Complications of Congenital Hernia in Pregnancy: A Case Report. Issue 3 (1st August 2019) - Vasquez, Daniela N.; Basualdo, María N.; Aphalo, Vanina M.; Carreras, Lucía P.; Plotnikow, Gustavo A.; Intile, Alfredo D.; Moreira, Joaquín
Abstract : Congenital hernias, frequently misdiagnosed during pregnancy, are potentially fatal and require prompt repair. A pregnant woman with medical history of repaired congenital hernia was admitted with misdiagnosis of preeclampsia. Physical examination and chest x-ray revealed a Bochdalek hernia. Transitory stabilization prompted surgeons to postpone hernia repair, but an urgent thoracotomy was required to relieve a subsequent bowel obstruction that was complicated by an intrathoracic colonic perforation. Emergent cesarean delivery was required with a good maternal and fetal outcome. A multidisciplinary team was present in the operating room. All monitoring catheters were placed in advance in the intensive care unit. During recovery, the patient experienced ventricular fibrillation, presumed to be a manifestation of takotsubo syndrome, which responded favorably to cardiopulmonary resuscitation.